2018
DOI: 10.46867/ijcp.2018.31.03.06
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Modified Monty Hall Dilemmas in Capuchin Monkeys, Rhesus Macaques, and Humans

Abstract: The Monty Hall Dilemma (MHD) is a simple probability puzzle famous for its counterintuitive solution. Participants initially choose among three doors, one of which conceals a prize. A different door is opened and shown not to contain the prize. Participants are then asked whether they would like to stay with their original choice or switch to the other remaining door. Although switching doubles the chances of winning, people overwhelmingly choose to stay with their original choice. To assess how experience and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Klein et al (2013) determined that the monkeys' (Macaca mulatta) performance indicated a substantial comparative similarity with human performance. The results of Watzek et al (2018) also showed considerable similarities between response patterns of capuchin (Cebus [Sapajus] apella) and rhesus macaques to human response patterns in both 3-door and 8-door conditions. Stagner and Zentall (2014) concluded that rats (Rattus norvegicus domestica, Sprague-Dawley strain), like pigeons, appeared to be influenced more by the overall probability of reinforcement, leading to similar performance between species.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…Klein et al (2013) determined that the monkeys' (Macaca mulatta) performance indicated a substantial comparative similarity with human performance. The results of Watzek et al (2018) also showed considerable similarities between response patterns of capuchin (Cebus [Sapajus] apella) and rhesus macaques to human response patterns in both 3-door and 8-door conditions. Stagner and Zentall (2014) concluded that rats (Rattus norvegicus domestica, Sprague-Dawley strain), like pigeons, appeared to be influenced more by the overall probability of reinforcement, leading to similar performance between species.…”
mentioning
confidence: 69%
“…Further studies examined whether this suboptimal tendency was exclusive to humans by testing nonhuman primates (Klein et al, 2013;Watzek et al, 2018) and rats (Stagner & Zentall, 2014). Klein et al (2013) determined that the monkeys' (Macaca mulatta) performance indicated a substantial comparative similarity with human performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, tasks are modified to be presented to the animals (at bare minimum, they have to be adjusted to provide training without verbal instruction) and at times, when humans are “back tested” on the modified task, they have shown different responses than in the original task; if the humans had not been tested on the modified task, we would have reached the erroneous conclusion that the nonhumans behaved differently than the humans. As an example of this, when given the same modified computer task to simulate the Monty Hall Dilemma, humans, similarly to capuchins and rhesus monkeys, quickly and consistently chose to switch doors, which is contrary to humans’ results when they were given the task with verbal instructions (Watzek et al, 2018). Thus, comparative studies require that all species perform the modified task by using the same (or as similar as possible) methodologies, including (or especially) humans (Smith et al, 2018).…”
mentioning
confidence: 95%
“…In this study, our goal was to determine whether capuchin and rhesus monkeys would expand their concepts of items that became less frequent over time using a methodology drawn from the human literature, and to directly compare the monkeys’ choices to humans’ by running human participants on the same task. Both monkey species are susceptible to some of the same decision-making biases as humans in some contexts that favor relative rather than absolute judgments (Chen et al, 2006; Egan Brad et al, 2016; Lakshminarayanan et al, 2008, 2011; Santos & Rosati, 2015; Watzek & Brosnan, 2020a, 2020b, 2020c), although this is not always the case (Cohen & Santos, 2017; Watzek & Brosnan, 2018; Watzek et al, 2018, 2019; Xu et al, 2011). For example, there is a tendency for both humans and monkeys to overvalue objects that they own over objects that they do not yet own, also known as the endowment effect (Lakshminarayanan et al, 2008).…”
mentioning
confidence: 99%